STRATEGI PEMERINTAH PROVINSI RIAU DALAM PENINGKATAN PENJAMINAN KREDIT MELALUI PT. JAMKRIDA RIAU TAHUN 2018 - Fidelis "; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
PT. Jamkrida Riau won the TOP BUMD 2018 for the 2018 TOP Jamkrida category and the 2018 TOP Builder (BUMD) award which was organized by Business News in Jakarta. PT. Jamkrida Riau has experienced growth in the amount guaranteed, the value of the guarantee and the proceeds of the IJP. However, in 2013-2020 PT Jamkrida Riau no longer added capital from the Riau Provincial Government so that it affected PT. Jamkrida Riau is doing its business.          This study aims to describe the Riau Provincial Government's Strategy in increasing credit guarantee through PT. Jamkrida Riau in 2018. This research uses a qualitative approach. The location of this research is in the office of PT. Jamkrida Riau, Pekanbaru City, Riau Province, Office of the Administration for the Economy and Human Resources (HR) of Riau Province and the DPRD Office of Riau Province. Sources of data in this study are informants and documents. The data collection technique is done by interview and documentation. While the data analysis technique was carried out by using descriptive qualitative analysis.          The results of this study indicate that there are two strategies used by the Riau Provincial Government in increasing credit guarantee through PT. Jamkrida Riau is an aggressive strategy and a diffensive strategy. The aggressive strategy is carried out by making programs to achieve targeted excellence / achievement, such as: the Riau Province Economic Bureau as the BUMD coach submits a request to the Riau Provincial DPRD for additional capital of PT. Jamkrida Riau and the management development of PT. Jamkrida Riau. Furthermore, a diffensive strategy is carried out by making programs to maintain the condition of excellence or achievement that has been achieved, such as: Facilitating health assessments, improving the quality of human resources, facilitating PT. Jamkrida Riau to cooperate with other parties and conduct surveillance. Keywords: Strategy, Riau Provincial Government and PT. Jamkrida Riau